1992
DOI: 10.3109/02713689209000753
|View full text |Cite
|
Sign up to set email alerts
|

Selective association of crystallins with lens 'native' membrane during dynamic cataractogenesis

Abstract: Plasma membrane with its associated extrinsic proteins was isolated from normal and cataractous rat lenses by centrifugation of the total water insoluble fraction from homogenized lenses on a discontinuous sucrose gradient. Membrane, which we call "native" membrane, was recovered mainly from the 25/45% sucrose interface. Development of the experimental U18666A cataract resulted in plasma membrane shifting to higher density (the 50/55% sucrose fraction) and great increases in the urea soluble protein content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…Although a certain basal level of crystallin association with fiber cell membranes occurs in normal lenses, massive binding of crystallins to lens membranes occurs in human cataracts (65). Interestingly, similar crystallin binding effects were observed for lens membranes isolated from rats treated with U18666A (66,67), suggesting that changes in membrane lipid composition were related to crystallin-membrane binding. Tang et al (68) recently demonstrated that increasing the cholesterol content of model membranes enriched with sphingomyelin attenuated the binding of ␣-crystallin; however, lens membrane-crystallin binding properties associated with cholesterol domains have not been examined.…”
Section: Discussionmentioning
confidence: 79%
“…Although a certain basal level of crystallin association with fiber cell membranes occurs in normal lenses, massive binding of crystallins to lens membranes occurs in human cataracts (65). Interestingly, similar crystallin binding effects were observed for lens membranes isolated from rats treated with U18666A (66,67), suggesting that changes in membrane lipid composition were related to crystallin-membrane binding. Tang et al (68) recently demonstrated that increasing the cholesterol content of model membranes enriched with sphingomyelin attenuated the binding of ␣-crystallin; however, lens membrane-crystallin binding properties associated with cholesterol domains have not been examined.…”
Section: Discussionmentioning
confidence: 79%
“…It may be relevant to cataractogenesis that as ␣ -crystallin becomes denatured, it binds more deeply into the membrane ( 128,134 ). The association of ␣ -crystallin with the membrane increases with age and cataract, as does light scattering ( 130,140,141 ). The increased association is thought not to be due to posttranslational modifi cations of ␣ -crystallin.…”
Section: ␣ -Crystallin Lipid Bindingmentioning
confidence: 99%
“…The prevailing explanation for these observations is that the amount of soluble ␣-crystallin available to bind partially denatured proteins becomes depleted with age, and the resulting high molecular mass aggregates slowly become insoluble. Interestingly, the amount of crystallin protein, especially ␣-crystallin, bound to the membrane also increases dramatically with increasing age and/or cataract formation (29,30). It could be that the progressive insolubilization of ␣-crystallin is due, in part, to increased membrane binding that is also associated with aging and cataract formation.…”
mentioning
confidence: 96%